Pelatihan sebagai Upaya Peningkatan Mutu Tenaga Kependidikan di Lingkungan Dinas Pendidikan Provinsi Daerah Khusus Ibukota Jakarta: Studi Di Pusat Pengembangan Manajemen Sekolah - Awalien Dhea Syafitrie; Amril Muhammad; Siti Rochanah (Program Studi Manajemen Pendidikan, 2016)
This research aimed to describe the planning and execution of training in improving the quality of education personnel in Jakarta. Research on quality managament be specified in two sub research focus is the planning of training and implementation of training activities in PPMS. The method used is a qualitative case research. The data obtained by researchers is through observation, depth interviews (depth interview), and documentation research. Key informant interviews were conducted at the Head Centre and supported by the informant support consists of the Head of Administration, Head of Executive Management Development Medium, instructor and trainees.The research concluded that 1) Planning of training undertaken in an effort to improve the quality of education personnel through the stages of training needs analysis, a coordination meeting between the committee and implementing units, define the training objectives, determining the training target, specify the subject matter, time, and number of participants, determine More specifically instructor with the materials according to their fields of expertise. Resulting from this process that the terms of reference of activities and proposal activities, criteria for participants and instructors criteria, the list of participants will be invited, syllabus and training schedules, training materials by the instructor, training rules and list of required facilities and infrastructure. 2) Implementation of the training activities carried out through pre-test phase – IN 1 – On the Job Learning – IN 2 – Post test up until the evaluation results come out in the form of certificates to the participants assessment. Output generated in the form of training implementation Accountability report along with photo documentation of training activities.PPMS should conduct a detailed analysis of requirement operating more hearts held trainin, set time allocation complex material material adjustments and trainer right, make a detailed schedule and disseminate the material shown to the participants which impacted the increasing skills from the training participants.